2015
DOI: 10.3389/fnagi.2014.00347
|View full text |Cite
|
Sign up to set email alerts
|

Age-group differences in speech identification despite matched audiometrically normal hearing: contributions from auditory temporal processing and cognition

Abstract: Hearing loss with increasing age adversely affects the ability to understand speech, an effect that results partly from reduced audibility. The aims of this study were to establish whether aging reduces speech intelligibility for listeners with normal audiograms, and, if so, to assess the relative contributions of auditory temporal and cognitive processing. Twenty-one older normal-hearing (ONH; 60–79 years) participants with bilateral audiometric thresholds ≤ 20 dB HL at 0.125–6 kHz were matched to nine young … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

60
488
9
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 372 publications
(565 citation statements)
references
References 206 publications
(248 reference statements)
60
488
9
8
Order By: Relevance
“…However, TFS1 scores at 850 Hz were correlated with absolute thresholds at 850 Hz (r = 0.67), even though audiometric thresholds were within the normal range, making it hard to rule out an effect of hearing loss. Füllgrabe et al (2015) eliminated confounding effects of hearing loss by testing young (18-27 years) and older (60-79 years) subjects with matched audiograms. Both groups had audiometric thresholds ≤ 20 dB HL from 0.125 to 6 kHz.…”
Section: Monaural Processing Of Tfsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, TFS1 scores at 850 Hz were correlated with absolute thresholds at 850 Hz (r = 0.67), even though audiometric thresholds were within the normal range, making it hard to rule out an effect of hearing loss. Füllgrabe et al (2015) eliminated confounding effects of hearing loss by testing young (18-27 years) and older (60-79 years) subjects with matched audiograms. Both groups had audiometric thresholds ≤ 20 dB HL from 0.125 to 6 kHz.…”
Section: Monaural Processing Of Tfsmentioning
confidence: 99%
“…It is hard to know whether this reflects a specific deficit in TFS processing or a more general reduction in processing efficiency. Füllgrabe et al (2015) also assessed sensitivity to ENV cues by measuring thresholds for detecting sinusoidal amplitude modulation imposed on a 4-kHz sinusoidal carrier. Modulation rates of 5, 30, 90, and 180 Hz were used to characterize the temporal-modulation-transfer function (TMTF).…”
Section: Monaural Processing Of Tfsmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence has shown that the loss of hearing thresholds due to changes in the periphery does not account for all the changes in hearing seen with age (Dubno et al 1984;Ruggles et al 2012;Fullgrabe et al 2015). Neural deficits due to loss of spiral ganglion and ribbon synapses (Sergeyenko et al 2013) or imbalances in the composition of neurotransmitters (Caspary et al 2008) in the central auditory pathway could account for the deficits seen in temporal processing and sound segregation at suprathreshold sound levels, which persist in subjects with clinically Bnormalĥ earing thresholds (Hind et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For a hearing loss that develops slowly and progressively, as is usually the case, the affected person may not notice the change in their hearing until it becomes rather severe. Consistent with this, many people who judge their own hearing to be 'normal' nevertheless have hearing loss that presumably leads to some hearing difficulty (see the supplementary material in Füllgrabe et al, 2015). Furthermore, self-report measures are affected by factors other than hearing ability, such as age and intelligence (Gatehouse, 1990).…”
Section: Predicting Self-reported Hearing Difficulty Based On Audiomementioning
confidence: 76%